Analisis Struktur Sel Cyanobacteria Pada Air Sawah di Kabupaten Karanganyar Berdasarkan Pengamatan Mikroskopis - Zahra Ramadhani Nur Aisyah; Maryam Salma As-syiifaurrahmah; Shifa Wahyu Ramadhani; Nopiya Ambar Setiyani; Fahrul Mustofa Ferdinaryoko; Antonius Marcello Candra Nelviany; Liss Dyah Dewi Arini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Cyanobacteria are photosynthetic prokaryotes commonly found in rice paddy ecosystems. They play a crucial role in the nitrogen cycle and help maintain the balance of agricultural ecosystems. This study aims to analyze the cell structure of cyanobacteria found in rice field water in Karanganyar Regency based on microscopic observations without using any staining treatments. Water samples were taken from a rice field in Karanganyar Regency during the active planting season. The observation was carried out using a light microscope with the wet mount method, without staining, to keep the cells in their natural condition. The observed parameters include the shape of the cells, the size of the cells, the arrangement of filaments or colonies, and other morphological characteristics that can be seen directly under a microscope. The observation results show that there are differences in the cell structure of cyanobacteria in the rice field water samples, reflecting the variety of cell shapes in that aquatic environment. This research aims to provide an initial overview of the structural characteristics of cyanobacteria cells in the rice field ecosystem of Karanganyar Regency. This will serve as a foundational reference for further studies in agricultural microbiology.